MANIFESTASI KEBUTUHAN BERTINGKAT TOKOH AYA KITO DALAM NOVEL ONE LITER OF TEARS MELALUI PENDEKATAN PSIKOLOGI HUMANISTIK ABRAHAM MASLOW - RACHMAWATI, DEVI SHINTA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Novel is one of literary fiction exciting and in demand by today's society. Novel One Liter of Tears can be analyzed through a variety of approaches one through the psychological approach, in this case the approach of humanistic psychology of Abraham Maslow. This study answers the formulation of the problem, namely, how the needs of multilevel manifestation Aya character in the novel One Litre of Tears through the approach of humanistic psychology of Abraham Maslow. Analyzed from the humanistic psychology of Abraham Maslow's theory of needs through stratified, the authors found evidence that suggests a figure of Aya Kito kink in the middle of her illness by using multilevel needs Maslow, include basic physiological needs, safety needs, the need for love and has, the need for self-esteem, and self-actualization needs. First is the physiological needs are met, such as food. Second, the need for security are met such as the protection and care of people around him to Aya. Then the third, the need for love and has successfully met the form of affection and love and support from people around him that never stops. The four requirements are met for self-esteem and motivation for the provision of support to the Aya from many quarters, and the last is the fulfillment of the need for self-actualization in the form of various kinds of things that have been done Aya to actualize himself in the middle of the limitations he has. For subsequent studies suggested to extend the analysis for example by analyzing the figures Shioka Kito, mother of Aya Kito, moral values ​​approach. Keyword : Psychology, Story needs, Novel, One Liter of Tears